Co-Fe/MIL-101(Cr) hybrid catalysts: Preparation and their electrocatalysis in oxygen reduction reaction. (3rd May 2019) - Li, Guoru; He, Xiaobo; Yin, Fengxiang; Chen, Biaohua; Yin, Huaqiang
Abstract: The development of highly efficient electrocatalysts with low cost for oxygen reduction reaction (ORR) is urgently required for metal-air batteries and fuel cells. In this work, FeCo/MIL-101(Cr) with various molar ratios of Fe/Co as hybrid catalysts was prepared by a facile and mild impregnation method. MIL-101(Cr) increased the specific surface areas of the hybrid catalysts, thus improving the dispersion of Fe and Co species at their surfaces. The effects of Fe and Co species on ORR activity of the hybrid catalysts were investigated. It is found that the synergistic effects between the well-dispersed Fe and Co species contribute mainly to ORR activity. More specifically, Fe species exert a partial-charge-transfer-activation effect on Co ones, which reduces the charge transfer resistance and thus improves the catalytic activity. As a result, FeCo/MIL-101(Cr) showed the excellent ORR activity, in which Co50 Fe50 /MIL-101(Cr) exhibited the superior ORR activity to the other prepared hybrid catalysts. Highlights: The Fe-Co/MIL-(Cr) hybrid catalysts were prepared via an impregnation method. The Fe and Co species are well dispersed in the MIL-101(Cr) supporter. The primary structures of the MIL-101(Cr) supporter are well preserved. The synergistic effect between Fe and Co species is vital for the ORR activity.